Inclusão audiovisual através do cinema de animação - Sergio Henrique Carvalho Vilaca (2006)
This task intends to contribute for understanding the social and cultural inclusion process through the movies, seeking for estimate initiatives that propose the cartoon (animation film) as element of educational experience at Brasilian public school. Actions that use the whole potential of the cartoon technicality to improve creativity and new educational method has been identified; as well as actions that connect the public school to the social and cultural institutions of audivisual in the non-governmental institutions.The Vilanimada Project is the subject of the study used for understanding the process of audiovisual inclusion at schools. Such project has been read up from the beginning to his conclusion. The experiences with cartoon study in Vilanimada Project and other else projects has been used for the elaboration of the textbook with substantial information about cartoon history, including its techniques and specific bibliography, specially how to draw up cartoon projects in low budget. This essay will support teachers in public schools as well as workshops using cartoon.